Sero-epidemiology of toxoplasmosis and associated risk factors among antenatal women in Ranchi, Jharkhand, India - Pratap, Rana; Aslami, Ahmad Nadeem; ., Manjushri; Sahu, Narayan Prasad (International Journal of Research in Medical Sciences, 2016)
Background: Toxoplasmosis seroprevalence in antenatal women has remained a contentious issue in Indian subcontinent. Bad obstetric history (BOH) is specific to women of childbearing age and can be caused by infection with Toxoplama gondii. In Jharkhand, scarce data exist for the roles of toxoplasmosis in the aetiology of adverse pregnancy outcome. Aim: To study the sero-epidemiology of Toxoplasmosis and associated risk factors among antenatal women attending antenatal clinic of a tertiary care hospital in Ranchi, Jharkhand, India. Methods: A case-control study was conducted on antenatal women attending antenatal clinic from the June 2010 to May 2011. The study group comprised 102 antenatal women of with BOH while the control group comprised 102 multiparous, age-matched antenatal women without BOH. Latex Slide agglutination test for antibodies to T.gondii was utilized. The research was approved by institutional ethical committee. Descriptive and inferential statistics was applied. Results: The overall seroprevalence of T.gondii among antenatal women was 15.19%, with significantly more in women with BOH (24.50%) as compared to women without BOH (5.88%). The seroprevalence in women with BOH gradually increased with advancing age: 8.33% in age less than 20 years to 50% in women older than 30 years. The seroprevalence increased steadily with number of BOH: 9.67% in women with one BOH to 37.50% in women with three or more BOH. Risk factors like Illiteracy, rural residence, owning a cat and non-veg dietary habit showed significant association. Conclusions: The seroprevalence of toxoplasmosis is high among antenatal women with BOH. Routine serological test is recommended for all pregnant women with BOH.